Daily QA in proton therapy using a single commercially available detector. (8th November 2014) - Lambert, Jamil; Bäumer, Christian; Koska, Benjamin; Ding, Xiaoning
Abstract : We present here a novel method for using a single device in the daily quality assurance (QA) of pencil beam scanning (PBS) proton beams and an improved method for uniform scanning (US). The device can be used to measure the spot position, spot sigma, range, output, collinearity of the X‐ray system and proton beam, and to QA the first scatterers and a number of other imaging and mechanical checks. We have performed the daily QA according to this procedure for more than six months in both a PBS gantry and a US gantry. All of the tests were found to be sensitive and accurate enough to determine if the property being tested is within the tolerance. The output has remained within the ± 2 % tolerance, with the majority of measurements within ± 1 %, and the range was within ± 0.5 mm . The collinearity of the proton beam in both gantries is within the ± 1 mm tolerance in both X and Y directions for all measurements. A novel procedure to measure the functionality of the first scatterers in the US gantry is included in the QA procedure. It was found to be sensitive enough to pick up the thinnest scatterer of 0.6 mm in both possible failure methods — when it always remains in the beam or in the case when it never goes into the beam. The daily QA procedure presented here can be implemented at PBS or US proton therapy centers with a minimal outlay for equipment and setup time. The procedure can be performed in less than 30 min, and has been found to be accurate and reliable enough for the QA of a proton therapy gantry before patient treatment every day. PACS number: 87.55.Qr